ZnAl2O4 supported on lychee-biochar applied to ibuprofen photodegradation. (January 2022) - Siara, Silvestri; Elvis, Carissimi; Harishkumar, Rajendran; Velayudhaperumal Chellam, Padmanaban
Highlights: The lychee peel biomass was used as a precursor in ibuprofen degradation. Biochar from lychee peel was used as carbonaceous support and facilitator for the free radical generation process. Adsorption/photocatalysis to ibuprofen was examined by RSM-CCF and practical tests. The composite showed superior photocatalytic efficiency due to the presence of functional groups present on the biochar surface. The biochar is essential for better efficiency in composite photocatalysis. Abstract: In this study, composites of biochar-ZnAl2 O4 produced by the pyrolysis of the lychee waste biomass were synthesized. The composites were characterized by XRD, FTIR, SEM, BET, and BJH. The biochar-ZnAl2 O4 composite was successfully formed and the efficiency was tested in adsorption and photocatalysis experiments. The adsorption equilibrium was obtained with a contact time of 60 min. Data on modeling and optimization of ibuprofen removal by statistical approach were fitted to quadratic equations using multiple regressions and analysis of variance (ANOVA). An RSM-CCF has been proposed for the enhanced removal of ibuprofen by adsorption followed by photocatalysis. The composite reached 100% efficiency of degradation of ibuprofen (20 mg L −1 ) in 120 min, under conditions of pH = 6.5, 25 °C, 1 g L −1 of composite. The ZnAl2 O4 supported significantly increased the composite adsorption performance and factors such as specific surface area (111.69 m 2 g −1 ), pore volume and pore size (mesoporous region) of the biochar synergistically promoted the photocatalytic activity of ZnAl2 O4, with k = 0.0093 min −1 . The adsorption and photocatalytic efficiencies were confirmed to contribute to the degradation of the ibuprofen aqueous solution by the radicals OH and O2 - in lower molecular weight by-products. The composite developed in this work showed that the support of ZnAl2 O4 in the biochar is essential to increase photoactivity, therefore, it has shown to be a promising material for adsorption and degradation of emerging pollutants such as the ibuprofen, avoiding transfer of pollution to another environmental medium. Graphical abstract: Image, graphical abstract